The use of passive drag to interpret variation in active drag measurements - Mason, B.; Formosa, D.; Raleigh, V. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
This study investigated if a measure of mean passive drag could explain the huge differences in propulsive force required by different swimmers to swim at a similar high velocity. Nineteen elite male and female national freestyle swimmers were subjects. The subject`s mean active and passive drag was measured at each swimmer`s top swimming pace. Stepwise regression analysis was used in the analysis. Passive drag was accepted into the equation to calculate mean propulsive force, prior to velocity being rejected. The correlation coefficient for the relationship between mean propelling force and mean passive drag was 0.77. This was statistically significant